Cancer-related FGFR2 overexpression and gene amplification in Japanese patients with gastric cancer. (13th July 2021) - Minashi, Keiko; Yamada, Takeshi; Hosaka, Hisashi; Amagai, Kenji; Shimizu, Yoshiaki; Kiyozaki, Hirokazu; Sato, Mikio; Soeda, Atsuko; Endo, Shinji; Ishida, Hiroyasu; Kamoshida, Toshiro; Sakai, Yoshinori; et al.
Abstract: Objective: Fibroblast growth factor receptor 2 (FGFR2) has been proposed as a novel druggable target in unresectable gastric cancer. FGFR2 alteration has been reported as associated with poor prognosis even in patients with gastric cancer who received systemic chemotherapy. This study aimed to evaluate the frequency of FGFR2 overexpression and gene amplification in clinical specimens from Japanese patients with recurrent or unresectable gastric cancer. Methods: This observational study enrolled patients who were histologically or cytologically confirmed with unresectable HER2-negative or unknown gastric or gastroesophageal junctional adenocarcinoma treated with at least one previous chemotherapy. FGFR2 overexpression and gene amplification in the specimens were evaluated by immunohistochemical staining and fluorescence in situ hybridization methods, respectively. Results: In a total of 173 eligible cases, FGFR2 immunohistochemistry score was evaluated as 0, 1, 2, 3 and 4 for 20, 80, 35, 28 and 10 cases, respectively. In 151 evaluable cases with FGFR2 immunohistochemistry scores of 1–4, FGFR2 copy number expressed as fluorescence in situ hybridization signals were detected as <4, ≥4 < 10 and ≥10 copies for 123, 16 and 12 cases, respectively. FGFR2 copy number showed an increasing tendency along with higher FGFR2 immunohistochemistry scores in the corresponding specimen. The response rate and time to treatment failure for first line chemotherapy did not have any obvious relationship to FGFR2 immunohistochemistry score and FGFR2 copy number. Conclusions: Although FGFR2 overexpression and gene amplification were shown in Japanese patients with unresectable gastric cancer, these alterations did not impact the effects of cytotoxic agents as first line chemotherapy. Abstract : A multicenter study evaluating the frequency of fibroblast growth factor receptor 2 overexpression and gene amplification in tumor specimen from Japanese patients with recurrent or unresectable gastric cancer.